Research progress on ferroptosis and PARP inhibitors in ovarian cancer: action mechanisms and resistance mechanisms - Jiqing Zhang; Jiqing Zhang; Dan Ouyang; Dan Ouyang; Mu Liu; Yuting Xiang; Zhongjun Li; Zhongjun Li (Frontiers in Pharmacology)
Ovarian cancer, a gynecologic malignancy with high mortality rates, faces persistent therapeutic challenges due to acquired resistance and frequent recurrence with conventional therapies. While poly (ADP-ribose) polymerase (PARP) inhibitors have primarily transformed clinical outcomes through the synthetic lethality mechanism, their long-term efficacy remains constrained by therapeutic resistance. Ferroptosis, a novel programmed cell death modality characterized by iron-dependent lipid peroxidation, has emerged as a promising therapeutic frontier in oncology. This review is the first to summarize the mechanisms of action and resistance associated with both ferroptosis and PARP inhibitors in ovarian cancer.